Aesthetics, Capitalism, and Control: TV Series as Spectacle - Wojtyna, Miłosz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
This article examines the contemporary TV series as a cultural form central to platform capitalism in general and to streaming services in particular. It argues that the aesthetic complexity of many key series—manifested in narrative composition, visual spectacle, and bingeable segmentation—is tightly bound to algorithmic control platforms aim to exercise, transforming viewer engagement into cognitive labour. Analysing the aesthetic foundations of binge-watching, as well as the logic of the recommendation systems that generates it, the article shows how aesthetic complexity conceals the commodification of attention, taste, and identity. Serial narratives become instruments of ideological control, turning interpretive effort into productive apathy. Drawing on Horkheimer and Adorno, as well as contemporary TV series criticism, the article frames the TV series as a spectacle of control characteristic of many trends in digital capitalism.